(untitled) - Jaderstrom, Susan (Boston, 2003)
The second edition of Business English at Work is designed to help you meet the challenges of a changing world, one in which the correct usage of English is tantamount to getting and holding a job. Working with these concepts, you will be fascinated by the activities and the exercises that relate to the Workplace Applications topics-a totally new learning approach relating business English to the world of work.
Keywords: Trung tâm Học liệu ĐHCT,English language; Tiếng Anh trong kinh doanh,Business English,Problems, exercises, etc